Hubungan Dukungan Kepala Keluarga Dengan Partisipasi Keluarga dalam Program Eliminasi (Minum Obat) Filariasis di Majasetra Kabupaten Bandung - Nadirawati (Jurusan Keperawatan FIKES UNSOED, 2011)
Based on the data from the years 2000-2009 in West Java, there were 980 people suffering from filariasis, and spread over several counties and cities. In Bandung, estimed around 2.7 million till of the 3.1 million are high risk of filariasis.The purpose of this research was to determine the relationship support of the family with family participation in the filariasis elimination program (taking medicine). The design of the study is a quantitative study using cross-sectional approach. The experiment was conducted from March to April using a questionnaire-shaped instrument. The sample determined by proportional random sampling technique with sample size were 139 respondents. Analysisof data through twostages of the univariate and bivariate with Chi-Square (Ã¯ÂÂ£2) with95% significance level. Research result revealed the head of a family that supports elimination program (taking medicine) filariasis, was 61.20%, and that did not support the filariasis elimination program (taking medicine) was 38.80%, 57.60% participating in the filariasiselimination program (taking medicine), and42.40% did not participate. There was correlation between the head of the family with families participation in the filariasis elimination program (taking medicine), (p-value: 0.000; ÃŽÂ±). Based on this researchit is suggest to the community nursesto improve thehealth promotion, counseling on filariasis elimination program, and motivation so that family can understand and aware the imporbuce of filariasis elimination program (taking medicine) that will impact on treatment success.